Longitudinal study of symptom burden in outpatients with advanced cancers based on electronic Patient-Reported Outcome (ePRO) platform: a single institution, prospective study protocol - Yan Wang; Qiuling Shi; Zimeng Li; Bingmei Wang; Lili Song; Lili Tang; Ying Pang; Xinkun Han; Chengcheng Zhou; Yuhe Zhou; Shuangzhi He; Yening Zhang; et al. (BMJ Open)
Introduction An electronic Patient-Reported Outcome (ePRO) platform is needed for implementing evidence-based symptom management in outpatients with advanced cancer. We describe the overall protocol and the methodology for measuring symptom burden, to provide critical parameters needed to implement symptom management on the ePRO platform.Methods and analysis The study focusses on patients with advanced lung cancer, stomach cancer, oesophagus cancer, liver cancer, colorectal cancer or breast cancer. The primary outcome is the change of symptom burden. MD Anderson Symptom Inventory, and other PRO instruments (Insomnia Severity Index, Hospital Anxiety and Depression Scale, 9-item Patient Health Questionnaire and EuroQol-5 dimensions-5 levels version) were used. The secondary outcomes include feasibility of using ePRO, symptom-related quality of life, reasons for no improvement of symptoms, defining frequency of PRO assessments and cut-points, items for screening and management of comorbidity and satisfaction with ePRO platform in patients and health providers. After initial outpatient visit for baseline assessment, ePRO system will automatically send follow-up notification seven times over 4 weeks to patients. The characteristics and changing trajectory of symptoms of patients will be described. Parameters for using PROs, such as optimal time points for follow-up and cut-off point for alert will be determined. The feasibility of ePRO platform to track the changes of target symptoms in outpatients will be evaluated.Ethics and dissemination The study protocol and related documents were approved by the Institutional Research Board (IRB) of Peking University Cancer Hospital on 13 February 2019 (2019YJZ07). The results of this study will be disseminated through academic workshops, peer-reviewed publications and conferences.Trial registration number ChiCTR1900023560.